An empirical assessment of common or usual names to label cell‐based seafood products - Hallman, William K.; Hallman, William K. (Journal of food science, 2020)
An important consideration in the commercialization of cell‐based meat, poultry, and seafood is what common or usual name to use on package labels to meet U.S. Food and Drug Administration (FDA) regulations. However, naming these products has been the subject of considerable debate. This study used a 3 × 10 between‐subjects online experiment involving a quota sample of 3,186 U.S. adult panel participants to test common or usual names using images of realistic packages of three types of seafood that a consumer might encounter in a supermarket. The terms tested were, “cell‐based seafood,” “cell‐cultured seafood,” “cultivated seafood,” and “cultured seafood” and the phrases, “produced using cellular aquaculture,” “cultivated from the cells of ____,” and “grown directly from the cells of ____,” where the blanks are filled by the name of the seafood product. Five criteria were used for evaluation, including each term's ability to: enable consumers to distinguish cell‐based seafood from wild and farmed fish, to signal potential allergenicity, be seen by consumers as an appropriate term to identify the product, not disparage either cell‐based or conventional products, and not evoke thoughts, images, or emotions that are inconsistent with the idea that the products are safe, healthy, and nutritious. The results showed that “cell‐based seafood” outperforms the other names tested. It enables consumers to recognize that the products are neither wild caught nor farm raised, signals potential allergenicity, is seen as an appropriate name for describing the technology/process, and it performs well with respect to measures of consumer acceptance, particularly in comparison to conventional products. Practical Application Creating consensus around a single common or usual name for cell‐based meat, poultry, and seafood products is clearly important both for regulatory reasons and for shaping public perceptions and understanding of the products that are labeled with it. Our findings suggest that “cell‐based” is the best common or usual name for seafood products that both meets FDA regulatory requirements and performs well with respect to potential consumer acceptance. Consistent use of this term by industry, advocates, and regulators would help orient consumers to what is likely to be a transformational food technology.